The Influence of Digital Literacy in Online Learning on Student Learning Outcomes - Irpan, Retno Megasafitri; Roesminingsih, Maria Veronika; Jacky, M (Indonesia Approach Education, 2023)
The study aimed to outline the effect of digital literacy on student learning outcomes within the context of online education, as well as to pinpoint the constraints related to digital literacy that affect student learning outcomes in online learning. The research utilized an ex post facto approach with a quantitative methodology. Data were gathered through questionnaires and academic performance assessments from a sample of 37. The data underwent analysis through descriptive techniques and simple linear regression. The initial findings revealed that the computed t value amounted to 0.625, which was less than the critical t value of 2.030. Consequently, no substantial influence of digital literacy on student learning outcomes was observed. This outcome emerged due to the limited understanding of digital media and the internet among students in the context of online learning. This limitation hindered them from effectively utilizing digital media and online resources to access information. The subsequent findings concerning the challenges posed by digital literacy within online learning unveiled two main obstacles: motivation/attitude and physical access. Within the motivation/attitude category, 4 students experienced isolation due to the absence of peers, 6 students struggled with comprehending the study material, and 3 students encountered issues related to time management, boredom, and fatigue. In terms of physical access, 5 students lacked the necessary digital devices, another 5 students were without internet data quotas, and 3 students faced difficulties with internet signal reception.